Politicians, political advisers and the vocabulary of public service bargains: Speaking in tongues?. (21st September 2016) - Shaw, Richard; Eichbaum, Chris
Abstract : Recent research on political advisers is characterized by an expansion beyond Westminster and clearer connections with proximate literatures. This article speaks to the second of these features by applying the Public Service Bargain (PSB) lens to minister/political adviser relationships in new ways. Extant PSB analyses either position political advisers as an independent variable influencing the core bargain between ministers and senior officials, or face difficulties when viewing advisers through existing perspectives developed to explain deals between politicians and public servants. Consequently, the nature of 'the bargain applying to political advisers' (Hood and Lodge 2006, p. 128) remains unclear. This article addresses that lacuna by deploying the reward, competence and loyalty dimensions of PSBs to specify the broad terms of the political adviser bargain, and considers the theoretical and empirical implications of such compacts.